2018
DOI: 10.1021/acsami.8b17607
|View full text |Cite
|
Sign up to set email alerts
|

Highly Compressible Cross-Linked Polyacrylamide Hydrogel-Enabled Compressible Zn–MnO2 Battery and a Flexible Battery–Sensor System

Abstract: The fast advancement in flexible and wearable electronics has put up with new requirements on the energy storage device with improved tolerance to deformation apart from offering power output. Despite the tremendous progress in stretchable energy storage devices, the compressional energy storage devices have indeed received limited research attention. In this work, an intrinsically compressible rechargeable battery was proposed using the Zn–MnO2 chemistry and a cross-linked polyacrylamide hydrogel electrolyte.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 50 publications
1
90
0
Order By: Relevance
“…It is a sign of the potential power source in the smart and wearable electronics. The results of mechanical strength of hydrogel electrolyte and electrochemical performance of the flexible battery and sensor system are presented in Figure 27 [208]. Li et al reported poly (acrylamide) grafted with gelatin hydrogel electrolytes for a zinc ion flexible battery.…”
Section: Polymer Hydrogel Electrolytes For Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a sign of the potential power source in the smart and wearable electronics. The results of mechanical strength of hydrogel electrolyte and electrochemical performance of the flexible battery and sensor system are presented in Figure 27 [208]. Li et al reported poly (acrylamide) grafted with gelatin hydrogel electrolytes for a zinc ion flexible battery.…”
Section: Polymer Hydrogel Electrolytes For Batteriesmentioning
confidence: 99%
“…Compressibility of the poly (acrylamide) hydrogel electrolyte (PAAm). (a) Images showing the elasticity of hydrogel under compressional and relaxed states; (b) resistance values of the poly (acrylamide) hydrogel electrolyte under different compressional strain values from 0 to 77.8%; (c,d) pictures showing the conductivity of hydrogel electrolyte under relaxed and compressional states with the ability to light a yellow light-emitting diode (LED) bulb; (e) optical images showing that two rechargeable Zn-MnO 2 batteries with poly (acrylamide) hydrogel electrolytes could be used for powering a luminescent panel under normal condition and with a 3-kg load on it; (f) comparison between the signals generated by the flexible sensor powered by the commercially available alkaline batteries and our compressible batteries without and with q load on top of it; (g) flexible smart wristband integrated from two ZIB modules and a flexible pressure sensor; (h) sensory signals of the smart wristband generated by human finger touch under different pressures on the device; (i) sensory signals of the smart wristband generated at different frequencies, from 0.3 to 4 Hz, by human finger touch[208].…”
mentioning
confidence: 99%
“…Currently, rechargeable aqueous zinc-ion batteries have attracted considerable attention for their high capacity, fast kinetics, and high safety [19][20][21][22]. These unique properties of zinc-ion batteries give us an inspiration for designing novel zinc-ion capacitors (ZIC) that is composed of zinc-ion insertion/extraction battery-type cathodes and suitable capacitor-type anodes.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic nonflammable aqueous electrolytes greatly revive aqueous batteries for their possible application in flexible configuration . Among various options of aqueous power sources, rechargeable Zn–MnO 2 batteries are emerging as one of the best candidates, owing to the high abundance and safety of both Zn and MnO 2 , as well as stable output voltage platform (≈1.5 V) of the whole device . Furthermore, the multiple ionic charge transport carriers enable Zn–MnO 2 batteries with large storage capacity and high energy density.…”
Section: Introductionmentioning
confidence: 99%